Properties of HI discs in the Auriga cosmological simulations - Marinacci, Federico; Grand, Robert J. J.; Pakmor, Rüdiger; Springel, Volker; Gómez, Facundo A.; Frenk, Carlos; White, Simon D. M. (Monthly notices of the Royal Astronomical Society, 2017)
We analyse the properties of the H i gas distribution in the Auriga project, a set of magnetohydrodynamic cosmological simulations performed with the moving-mesh code arepo and a physics model for galaxy formation that succeeds in forming realistic late-type galaxies in the 30 Milky Way-sized haloes simulated in this project. We use a simple approach to estimate the neutral hydrogen fraction in our simulation set, which treats low-density and star-forming gas separately, and we explore two different prescriptions to subtract the contribution of molecular hydrogen from the total H i content. The H i gas in the vast majority of the systems forms extended discs although more disturbed morphologies are present. Notwithstanding the general good agreement with observed H i properties - such as radial profiles and the mass-diameter relation - the Auriga galaxies are systematically larger and more gas-rich than typical nearby galaxies. Interestingly, the amount of H i gas outside the disc plane correlates with the star formation rate, consistent with a picture where most of this extra-planar H i gas originates from a fountain-like flow. Our findings are robust with respect to the different assumptions adopted for computing the molecular hydrogen fraction and do not vary significantly over a wide range of numerical resolution. The H i modelling introduced in this paper can be used in future work to build artificial interferometric H i data cubes, allowing an even closer comparison of the gas dynamics in simulated galaxies with observations.
Gesehen am 15.02.2019